2010
DOI: 10.1248/cpb.58.628
|View full text |Cite
|
Sign up to set email alerts
|

New Phenanthrenes and Stilbenes from Dendrobium loddigesii

Abstract: " which is the dried stem of genus Dendrobium, has been used to treat fever, inflammation, and similar conditions. 1,2) Within genus Dendrobium, Dendrobium nobile LINDL. and D. officinale K. KIMURA et MIGO were originally used as "Xiao Huang Cao Shi Hu." However, these plants are very rare, and therefore, other plants of genus Dendrobium, including D. loddigesii ROLFE, D. moniliforme (L.) SW., and D. lohohense TANG et WANG, have also been distributed as "Xiao Huang Cao Shi Hu" in medicinal herb markets in Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…Its molecular formula was determined to be C 21 H 22 O 8 from the quasi molecular ion peak at 425.1208 in the HR-ESI-MS ([M+Na] + ). Its UV maxima absorptions at 214.5, 254.0, 283.5, and 313.5 nm were similar to phenanthrene derivatives (Ito et al, 2010). Its 1 H NMR (Table 1) signals at 7.44 (t, J = 7.6 Hz, H-7), 7.40 (d, J = 7.6 Hz, H-8), 7.13 (dd, J = 7.6, 1.4 Hz, H-6) showed a 1,2,3-trisubstituted phenyl ring.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Its molecular formula was determined to be C 21 H 22 O 8 from the quasi molecular ion peak at 425.1208 in the HR-ESI-MS ([M+Na] + ). Its UV maxima absorptions at 214.5, 254.0, 283.5, and 313.5 nm were similar to phenanthrene derivatives (Ito et al, 2010). Its 1 H NMR (Table 1) signals at 7.44 (t, J = 7.6 Hz, H-7), 7.40 (d, J = 7.6 Hz, H-8), 7.13 (dd, J = 7.6, 1.4 Hz, H-6) showed a 1,2,3-trisubstituted phenyl ring.…”
Section: Resultsmentioning
confidence: 80%
“…Its IR absorption at 3441 cm À1 showed the presence of hydroxyl groups. Its UV maxima absorptions at 214.5, 254.0, 283.5 and 313.5 nm again indicated a phenanthrene derivative (Ito et al, 2010). The NMR spectroscopic data confirmed that compound 3 possessed the same skeleton and substitution mode as compound 1, except that it contained an extra sugar residue.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…[3] Plants of the genus Dendrobium (Orchidaceae) have been known to produce a wide variety of chemical compounds, including Submission Date: 30- Accepted Date: 24-3-2014 alkaloids, bibenzyls, phenanthrenes, fluorenones, steroids, sesquiterpenes, coumarins and polysaccharides. [4,5] Recent biological studies have shown that some Dendrobium species possess anti-platelet aggregation, anti-fibrotic, free radical scavenging, immunomodulatory and cytotoxic activities. [5][6][7][8] Dendrobium williamsonii Day &Rchb.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Recent biological studies have shown that some Dendrobium species possess anti-platelet aggregation, anti-fibrotic, free radical scavenging, immunomodulatory and cytotoxic activities. [5][6][7][8] Dendrobium williamsonii Day &Rchb. f. is known in Thai as "Ueangngoen sad".…”
Section: Introductionmentioning
confidence: 99%